A Snapshot of 126 CPAE Members’ Social Media Habitus for Professional Networking and Collaborations Online - Kang, Haijun (My University, 2017)
This online survey was developed to help the Commission of Professors of Adult Education (CPAE) Executive Committee better understand current CPAE community members’ social media habitus for professional networking and collaborations online. 126 CPAE community members completed the survey during the two-week window in February 2017. The major findings are: -97% of the survey respondents are on various social media platforms for professional networking and collaboration purposes. -Facebook (FB) and LinkedIn are the two most popular social media platforms used by the survey respondents with the popularity scores of 28% and 29% respectively. -63% of the survey respondents self-identified as FB users and 67% self-identified as LinkedIn users. -Among the survey respondents, 78% of the FB users and 40% LinkedIn users are on the corresponding social media platforms more than 3 times a week. -Based on the survey responses, a list of social media selection criteria is developed with 11 things to consider when selecting a social media platform(s) for professional networking and collaboration use.
A Report to The Commission of Professors of Adult Education (CPAE) Executive Committee